THE DIFFERENCE BETWEEN ACUPUNCTURE THERAPY AND KATUK LEAF EXTRACT ON BREAST MILK PRODUCTION IN BREASTFEEDING MOTHERS IN DUWETAN NGUNUT JUMANTONO KARANGANYAR - Sholihah, Imrok Atus; Widyastari, Sri (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Background: Suboptimal breastfeeding accounts for 45% of deaths. Various treatments can be done to increase the amount of breast milk production, both pharmacological and non-pharmacological. One of the efforts that can be done to increase the rate of secretion and production of breast milk is through the use of traditional herbal medicines such as katuk extract (Sauropus androgynus). Acupuncture significantly improves exclusive breastfeeding. Acupuncture therapy can be done to increase the hormone prolactin in breastfeeding.Objective: To determine the difference between acupuncture therapy and katuk leaf extract on increasing breast milk production in breastfeeding mothers in Duwetan, Ngunut, Jumantono, Karanganyar. Time and Place: April-May 2021, at Duwetan, Ngunut, Jumantono, Karanganyar. Subjects: The research sample taken was 40 mothers who were in the breastfeeding phase in Duwetan, Ngunut, Jumantono, Karanganyar.Methods: This study is a experimental study with a Pretest-Posttest Control Group design. Statistical test using univariate analysis and bivariate analysis using independent t-testResults: After the intervention, milk production (based on baby's weight) in the acupuncture group was higher (Mean= 4.029,50; SD= 392,33) than in the katuk leaf extract group (Mean= 3.450,50; SD= 405,08). There was a difference in breast milk production in the acupuncture group and the katuk leaf extract group (p<0,001). The administration of acupuncture increased milk production significantly with an effect value (ES = 1,45) compared to the administration of katuk leaf extract.Conclusion: There is a difference between acupuncture therapy and katuk leaf extract on breast milk production in breastfeeding mothers.